The Use of High-Speed Videography to Generate Angle-Time and Angle-Angle Diagrams for the Study of Equine Locomotion - Martinez-del Campo, L. J.; Kobluk, C. N.; Greer, Nancy; Trent, Ava M.; Stoner, Lela June; Wickstrom, L.; Loch, Deborah (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
IntroductionHigh-speed videography was used to generate angle-time and angle-angle diagrams to provide the basis for a better subjective and objective understanding of the locomotor function of the horse. Intra- and interlimb coordination patterns were analyzed in a group of ten clinically sound racing Thoroughbreds. For lateral video recording, reflective markers were glued over the axis of rotation of the fore- and hindlimb joints of the ten horses. All horses were filmed simultaneously from both sides (right and left). Means and standard deviations were calculated for the minimum, the maximum and the range of motion values for the angle excursions of each joint. Angle-time and angle-angle diagrams were highly repeatable over the eight to nine strides videotaped for each horse and showed a very characteristic shape with minor variations between individual horses. When comparing right versus left sides, horses exhibited varying levels of significant asymmetry.
Keywords: Gait analysis; high-speed videography; angle-angle diagram; equine locomotion